Dangerous othering in Meg Vandermerwe's Zebra crossing: Ubuntu – ideals and realities of the 2010 FIFA World Cup. Issue 1 (2nd January 2016) - Wilkinson, Robyn
ABSTRACT: This article explores the process of 'othering' in Meg Vandermerwe's 2013 novel Zebra crossing. Othering is defined as a discursive practice in which one social group defines another in an inferior way. The novel is narrated by Zimbabwean-born albino, Chipo, who crosses the border into South Africa shortly before the start of the 2010 FIFA World Cup. Far from finding the better life she had hoped for there, Chipo is instead met with prejudice and disdain from locals. Through her portrayal of Chipo's life as an illegal immigrant in Cape Town, Vandermerwe shows that while apartheid is over, social division and inter-group conflict are not. All the while juxtaposing this reality against the backdrop of the World Cup and the ubuntu ideals it championed but failed to deliver, Vandermerwe exposes how wide the gap is between theory and practice, ideology and lived reality. Highlighting the power of discursive practices like othering to produce real and violent consequences, Vandermerwe warns that if we do not truly embrace the values of forgiveness, compassion and acceptance, we face a dark future in which a cycle of conflict and injustice is repeated instead of being broken.